Future Perspectives for Antiangiogenic Therapy in Retinal Diseases - M. V. Budzinskaya; A. A. Plyukhova (Oftalʹmologiâ, 2021)
The World Health Organization considers eye disorders as the serious problem of our time [1]. According to world statistics, the number of people with visual impairment is 1.3 billion, most of this number are people over 50 years old [2]. Over the past 20 years, developments in the treatment of AMD and fundus diseases have advanced and include drugs such as vascular endothelial growth factor inhibitors. The molecular structures of drugs intended for intravitreal use range from RNA aptamers (pegaptanib) to full-length monoclonal antibodies (mAb: bevacizumab) to Fab fragments (ranibizumab) and an antibody conjugate (aflibercept). In addition, single-chain variable fragment (scFv: brolucizumab), bispecific monoclonal antibody (faricimab) and DARPin (abigar pegol) show promising results in clinical trials.[6],[7] Brolucizumab (RTH258) was developed by ESBATech (ES-BATech AG — Schlieren ZH, Switzerland) originally under the name ESBA1008, an inhibitor of the humanized single chain antibody fragment (scFv) of all isoforms of vascular endothelial growth factor-A (VEGF-A). [6],[7],[11]. The Faricimab (ROCHE, Switzerland) molecule is characterized by the presence of a bispecific antibody that simultaneously binds to both VEGF-A and Ang-2; the drug consists of an anti-Ang-2 antigen-binding fragment (Fab), an anti-VEGF-A Fab and a crystallizing modified fragment (Fc region) with a total size of 150 kDa. This “crossover” effect provided high affinity for both targets while also maintaining a good stability profile compared to natural antibodies [8]. Abicipar Pegol (Abicipar, Allergan. Dublin, Ireland) is a DARPin aimed at binding all VEGF-A isoforms, like ranibizumab. It has a higher affinity and a longer half-life from the eye than ranibizumab (>13 days versus 7.2 days), making it a potential drug with a longer duration of action and the need for less frequent injections [15]. In this article, we tried to summarize the literature data on new anti-VEGF drugs being developed and ready for release. We hope that the appearance of these drugs on the market will make it possible to reduce the injection load on the patient and optimize their material costs.